Biological Nitrification Inhibition (BNI): Phenotyping of a Core Germplasm Collection of the Tropical Forage Grass Megathyrsus maximus Under Greenhouse Conditions - Villegas, Daniel; Arevalo, Ashly; Nuñez, Jonathan; Mazabel, Johanna; Subbarao, Guntur; Rao, Idupulapati; De Vega, Jose; Arango, Jacobo (Frontiers in Plant Science, 2020)
Modern intensively managed pastures that receive large external nitrogen (N) inputs account for high N losses in form of nitrate (NO3-) leaching and emissions of the potent greenhouse gas nitrous oxide (N2O). The natural plant capacity to shape the soil N cycle through exudation of organic compounds can be exploited to favor sustainability by promoting N retention without affecting productivity. In this study, we estimated the relationship between biological nitrification inhibition (BNI), N2O emissions and plant productivity for 119 germplasm accessions of Guineagrass (Megathyrsus maximus), an important tropical forage crop for livestock production. This relation was tested in a greenhouse experiment measuring BNI as i) rates of soil nitrification; ii) abundance of ammonia-oxidizing bacteria (AOB) and archaea (AOA); and iii) the capacity of root tissue extracts to inhibit nitrification in vitro. We then measured N2O emissions, aboveground biomass and forage nutrition quality parameters. Reductions on nitrification activity ranging between 30 to 70 % were found across the germplasm collection of M. maximus. Accessions with low nitrification rates showed a lower abundance of AOB as well as a reduction in N2O emissions compared to accessions of high nitrification rates. The BNI capacity was not correlated to N uptake of plants, suggesting that in this grass species may occur intraspecific variation in the exploitation of different N sources. A group of accessions (cluster) with the most desirable agronomic and environmental traits among the collection was identified for further field validation. These results provide evidence of the ability of M. maximus to suppress soil nitrification and N2O emissions and their relationship with productivity and forage quality, pointing a way to develop N conservative improved forage grasses for tropical livestock production.